2007
DOI: 10.1086/521275
|View full text |Cite
|
Sign up to set email alerts
|

A Defect in the Ionotropic Glutamate Receptor 6 Gene (GRIK2) Is Associated with Autosomal Recessive Mental Retardation

Abstract: Nonsyndromic mental retardation is one of the most important unresolved problems in genetic health care. Autosomal forms are far more common than X-linked forms, but, in contrast to the latter, they are still largely unexplored. Here, we report a complex mutation in the ionotropic glutamate receptor 6 gene (GRIK2, also called "GLUR6") that cosegregates with moderate-to-severe nonsyndromic autosomal recessive mental retardation in a large, consanguineous Iranian family. The predicted gene product lacks the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
109
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(117 citation statements)
references
References 33 publications
1
109
1
2
Order By: Relevance
“…Using primary neuronal cultures, we have demonstrated that UPF3B is present in nucleus, cytoplasm and most importantly in dendritic spines, which allow the formation of synaptic connections between neurons and which contain the postsynaptic density. Strikingly, a recent study performed by Chan et al 32 indicated that UPF3B depletion of HeLa cells by RNAi led to an upregulation by at least threefold for numerous transcripts, including particularly two genes previously involved in MR and/or autism, the GRIK2 and SHANK3 genes, 34,35 coding for postsynaptic receptor and scaffolder, respectively. 36,37 Although direct or indirect deregulation of GRIK2 and/or SHANK3, in patients with UPF3B mutations, would be very interesting to see in this context, our preliminary microarray data from patients LCLs do not support it (JG, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Using primary neuronal cultures, we have demonstrated that UPF3B is present in nucleus, cytoplasm and most importantly in dendritic spines, which allow the formation of synaptic connections between neurons and which contain the postsynaptic density. Strikingly, a recent study performed by Chan et al 32 indicated that UPF3B depletion of HeLa cells by RNAi led to an upregulation by at least threefold for numerous transcripts, including particularly two genes previously involved in MR and/or autism, the GRIK2 and SHANK3 genes, 34,35 coding for postsynaptic receptor and scaffolder, respectively. 36,37 Although direct or indirect deregulation of GRIK2 and/or SHANK3, in patients with UPF3B mutations, would be very interesting to see in this context, our preliminary microarray data from patients LCLs do not support it (JG, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…6 Until now, 26 significantly linked non-specific intellectual disability of autosomal recessive inheritance (NS-ARID) loci were described, [7][8][9][10] and only 10 genes (six of them located in described regions) were identified: PRSS12 (OMIM#606709, on 4q26, former MRT1), CRBN (OMIM#609262, on 3p26, former MRT2), CC2D1A (OMIM#610055, on 19p13.12, former MRT3), ST3GAL3 (OMIM#606494, on 1p34.3), GRIK2 (OMIM#138277, on 6q16, former MRT6), TUSC3 (OMIM#601385, on 8p22, former MRT7), ZNF26 (no OMIM#, on 19q13.2), TRAPPC9 (OMIM#613192, on 8q24, former MRT13), ZCH14 (OMIM# 613279, on 14q31.3), and TECR (MIM*610057 on 19p13.12) (Figure 1). 1,[11][12][13][14][15][16][17][18][19] Taking into account that over 90 genes are responsible for only about 40% of X-chromosomal recessive ID cases, and that about half of the estimated 22 000 human genes are expressed in the brain, the total number of ARID genes may run into the hundreds. 1 Considering the heterogeneity observed in previous linkage studies, and the fact that the so far identified genes do not account for a significant fraction of NS-ARID cases, systematic approaches are the most promising strategy to identify further genes.…”
Section: Introductionmentioning
confidence: 99%
“…4 GRIA2 encodes the GLUR2 subunit of AMPA (a-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid) receptors and is mainly expressed in brain. 5 GLUR2 controls important biophysical properties of AMPA receptors and is involved in learning, memory and synaptic plasticity.…”
Section: Introductionmentioning
confidence: 99%